Ensinar e aprender ortografia no 3º ano do ensino fundamental em uma escola de Jaguarão/RS - Vieira , Betânia Rondan (2022)
This Critical-Reflective Report is the result of research that proposed pedagogical practices that stimulate spelling learning in the 3rd year of Elementary School. The main objective delimited by the research was to analyze the learning about spelling of students of the 3rd year of Elementary School, promoted through pedagogical practices that stimulate reflection and understanding about regularities and irregularities of Portuguese words. Research theoretical assumptions are based on current conceptions of literacy in Brazil, which guide orthography learning through reflective practices (MORAIS, 1998) for the development of metalinguistic awareness (GUIMARÃES; ROAZZI, 2007; SOARES, 2020b).The methodology adopted for the research is a pedagogical intervention (DAMIANI, 2012) with qualitative data analysis (LÜDKE and ANDRÉ, 1986). The intervention actions were carried out from insertions in a 3rd year class of Elementary School in General Antônio de Sampaio Municipal Elementary School. Pedagogical proposals were made that stimulate reflections about regularities and irregularities of Portuguese words. For data collection, the following instruments were used: the questionnaire answered by the holder teacher of the class, the teacher's plans, the written records of the apprentices and the recordings of the encounters. The treatment of the data collected in the research was done from the discursive textual analysis (MORAES, 2003). With the analysis it was possible to identify the writing hypothesis of the learners as well as each one's understanding of the Alphabetic Writing System. In addition, it was possible to verify the construction of some learning about the contextual regularities built from the development of metalinguistic awareness.